Μελέτη συστήματος μετάδοσης κίνησης από εκτονωτή οργανικού κύκλου Rankine (ORC) σε συμπιεστή ψυκτικής μηχανής (VCC) - Μπίτσης, Ευστράτιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Θερμότητας. Εργαστήριο Ατμοκινητήρων και Λεβήτων, 2015)
The purpose of this diploma thesis is the power transmission design concerning the connection among a scroll expander from an Organic Rankine Cycle, a scroll compressor from a Vapor Compression Cycle and an induction generator. These machines are parts of a small scale trigeneration system. Firstly, two semi-empirical models were developed, in order to simulate the scroll machines (compressor and expander) and then, two commercial machines were selected. The validation of these models requires experimental data for the used parameters calculation. Since it was not possible to conduct experiments for the specification of the model parameters, values were extracted from the existing literature. Consequently, the two thermodynamic systems were designed and the output power of the expander and the input power of the compressor were calculated, at the design point. For the power transmission, a wide variety of sub-systems are available, such as gears, belts and chains. In this regard, two mechanical subsystems were designed, one with belt drive and one with gears drive containing all the required parts. Finally, the operation of the cooling system when the load of the evaporator changes was investigated and compared with the system where the compressor is attached to an electric motor.